(untitled) (Patan Pragya, 2025)
This paper analyzes the socioeconomic and demographic variables that affect the use of post-natal care (PNC) within two days (42 hours after delivery) of delivering their newborns in Karnali Province by using the data on the Nepal Demographic and Health Survey (NDHS) 2022. PNC is necessary in the early stages of pregnancy to prevent complications in the post-partum period and minimize maternal and neonatal deaths, but the coverage is unevenly distributed among disadvantaged. The analytical design was cross-sectional and a weighted sample of 216 women who had recently given birth to live was used. The descriptive statistics were employed to investigate the PNC interest among different subgroups of the population and multivariate logistic regression was applied to determine the factors related to use of PNC. The findings indicated that a lower proportion of 58.3 percent of the women received PNC in two days. Women between the ages of 20 and 29 years of age, the first time mothers, women who were better educated and the women who resided in more affluent households were more likely to utilize the services. The regression analysis found that maternal education and household wealth were the strongest predictors of timely postnatal care (PNC). Women with high education were over four times more likely to receive PNC than those with low education. Similarly, women from the richest households had higher chances of receiving PNC compared to poorer households. Caste/ethnicity, religion, and residence were not statistically significant factors. It highlights socioeconomic differences in PNC use and shows that policies are needed to improve education, reduce poverty, and increase maternal health access in rural areas.